A Historical Reconstruction of the Essential Characteristics of Nigeria’s Federal Budget, 1954-2000 - Ogunyemi, Adetunji Ojo (Modern Africa: Politics, History and Society, 2017)
This study analyses the basic features that characterised the budget and budgeting processes of the Federal Republic of Nigeria from 1954 to 2000. The characteristics are discussed around the theme of public financial accountability and transparency in governance. The study establishes that the characteristics of Nigeria’s budgetary processes during the period under review conditioned the fiscal behaviour of the country’s federal finances and contained peculiar fiscal and legal dimensions worthy of emphasis. The study relies on a method of historical chronology and exegetical analysis of all identified features contained in the forty-seven Appropriation Acts passed and enforced during 1954-2000 in identifying common fiscal characters in them and arriving at its findings and conclusions. The study found that repetitive budgeting, extra-budgetary expenditure and the circumvention of the laws on public accountability especially after independence in 1960 were the most visible negative features of the Nigerian budget during the period studied.